Smart mems and sensor systems - Gaura, Elena (Online access with JISC subscription agreement: Knovel., 2006)
In recent years, MEMS have revolutionized the semiconductor industry, with sensors being a particularly buoyant sector. Smart MEMS and Sensor Systems presents readers with the means to understand, evaluate, appreciate and participate in the development of the field, from a unique systems perspective. The combination of MEMS and integrated intelligence has been put forward as a disruptive technology. The full potential of this technology is only evident when it is used to construct very large pervasive sensing systems. The book explores the many different technologies needed to build such systems and integrates knowledge from three different domains: MEMS technology, sensor system electronics and pervasive computing science. Throughout the book a top-down design perspective is taken, be it for the development of a single smart sensor or that of adaptive ad-hoc networks of millions of sensors. For experts in any of the domains named above the book provides the context for their MEMS based design work and an understanding of the role the other domains play. For the generalist (either in engineering or computing) or the technology manager the underpinning knowledge is provided, which can inform specialist decision making.